Solvent- and catalyst-free transamidations of unprotected glycosyl carboxamides. Issue 43 (25th October 2019) - Bensalah, Fouzia Ouadah; Bil, Abed; Wittine, Karlo; Bellahouel, Salima; Lesur, David; Markovic, Dean; Laclef, Sylvain
Abstract : New green and atom efficient transamidation reactions of various glycosyl carboxamides with primary and secondary amines are described. Abstract : The transamidation reactions of unprotected mono- and disaccharidic carboxamides with various primary and secondary arylic, heterocyclic or aliphatic amines are described. This new method is green and atom efficient and gives good to high yields. Notably, the conditions do not require either a solvent or a catalyst and give ammonia as a single by-product. The described coupling reaction is compatible with a variety of functional groups and was used in the synthesis of various glycosidic derivatives and biologically relevant glycolipids. A plausible reaction mechanism involving an intermolecular H-bond activation of the starting carboxamides is proposed.